An intervention trial targeting methadone maintenance treatment providers to improve clients' treatment retention in China. (1st January 2019) - Li, Li; Wu, Zunyou; Liang, Li-Jung; Lin, Chunqing; Luo, Sitong; Cao, Xiaobin; Hsieh, Julie; Rou, Keming
Highlights: Methadone maintenance treatment (MMT) provider training intervention has shown promise in reducing client dropout. The intervention gives providers client-centered communication skills and tools. MMT providers can be trained to deliver individual sessions to engage clients. The intervention has potential to improve MMT provider training and services. Abstract: Background: Service providers including doctors, nurses, and other healthcare professionals play an essential role in methadone maintenance treatment (MMT). This study evaluated the impact of an intervention targeting MMT providers on their clients' treatment retention. Methods: This study was conducted in 68 MMT clinics in five provinces of China with 36 clients randomly selected from each clinic. The clinics were randomized to intervention or control condition. The MMT CARE intervention started with group sessions to enhance providers' communication skills. The trained providers were encouraged to conduct individual sessions with clients to promote treatment engagement. The outcomes, which include client retention (main outcome) and their reception of provider-delivered individual sessions (process outcome), were measured over a 24-month period. Results: Significantly fewer intervention clients dropped out from MMT than control clients during the study period (31% vs. 41%; p < 0.0001). Dropout hazard was significantly lower in the intervention condition compared to the control condition (HR = 0.71, 95% CI: 0.57, 0.89). More intervention clients had individual sessions than control clients (93% vs. 70%; p < 0.0001). Having individual sessions was associated with a significantly lower dropout hazard (HR = 0.30, 95% CI: 0.23, 0.40). The intervention clients had a significantly lower dropout hazard than the control clients if they started the individual sessions during the first six months (HR = 0.68, 95% CI: 0.51, 0.90). Conclusions: The MMT CARE intervention focusing on provider capacity building has demonstrated efficacy in reducing clients' treatment dropout. This study sheds light on MMT service improvement in China and other global community-based harm reduction programs.